THE IMPACT OF TAX PLANNING AND DEFERRED TAX EXPENSE TOWARD EARNINGS MANAGEMENT AT TRADE, SERVICES AND INVESMENT COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Friyan Satria (Journal of Accounting and Management Innovation, 2023)
This research is conducted with purpose to know whether tax planning and deferred tax expense have impact on earning management in trade, services and investment companies registered in Indonesia Stock Exchange. Population in this research is trade, services and investments companies in Indonesia Stock Exchange for year 2018-2020 in amount of 164 companies. The company used as the sample is 38 companies with the amount of research data is 114 data for period 2018-2020. Data analysis method implemented in this research is multiple linear regression analysis method. There are some conclusions of this research. Tax planning has no significant impact partially on earning management at trade, services and investments companies on the Indonesia Stock Exchange. Deferred tax has significant impact partially on earning management at trade, services and investments companies on the Indonesia Stock Exchange. Tax planning and deferred tax have significant impact simultaneously on earning management at trade, services and investments companies in Indonesia Stock Exchange.